Understanding the magnetic anisotropy for linear sandwich [Er(COT)]+-based compounds: a theoretical investigation. Issue 8 (8th February 2022) - Ding, Man-Man; Shang, Tao; Hu, Rui; Zhang, Yi-Quan
Abstract : High axial symmetry is also preferable for prolate shaped Er III to behave as a high-performance SIM. A medium ligand ring of benzene is preferable for prolate shaped Er III ion, which can induce the modest energy splitting and the small TA-QTM. Abstract : A series of linear sandwich single-ion magnets containing [Er(COT)] + fragment were selected to probe the magneto-structural correlations using ab initio methods. For prolate shaped Er III ion, an equatorially coordinating geometry is preferable to achieve high axial anisotropy. Our calculations confirm that the increasing transversal crystal field (CF) induced by equatorial ligands truly enhances the energy barrier. However, if we continue to strengthen the transversal CF in the equatorial plane, the energy barrier inversely decreases. Our further results show that a medium ligand ring of benzene is preferable for prolate shaped Er III ion, which can induce the modest energy splitting and the small temperature-assisted quantum tunneling of magnetization. Although the obtained energy barrier of 343.1 cm −1 for our created model [(C6 H6 )Er(COT)] + is the largest, it is also much smaller than the Dy III -based compounds.